2011
DOI: 10.1007/s12265-011-9291-1
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Acellular Hydrogels for Cardiac Repair

Abstract: Injectable hydrogels are being developed as potential translatable materials to influence the cascade of events that occur after myocardial infarction. These hydrogels, consisting of both synthetic and natural materials, form through numerous chemical crosslinking and assembly mechanisms and can be used as bulking agents or for the delivery of biological molecules. Specifically, a range of materials are being applied that alter the resulting mechanical and biological signals after infarction and have shown suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 97 publications
1
143
0
2
Order By: Relevance
“…The injectable hydrogels are well known for high tissue-like water content, limited surgical invasion and bulking effects. 6 The proper porosity (to promote immunoisolation and metabolite diffusion), 7 and degradation proportional to allow the cell growth and moldability to ll the defective regions are some of the essential requirements for tissue engineering. 8 The hydrogels can be prepared from both natural and synthetic polymers by physical (polyelectrolyte complexation, hydrogen bonding and hydrophobic association) or chemical (free radical polymerization, irradiation crosslinking) methods.…”
Section: Introductionmentioning
confidence: 99%
“…The injectable hydrogels are well known for high tissue-like water content, limited surgical invasion and bulking effects. 6 The proper porosity (to promote immunoisolation and metabolite diffusion), 7 and degradation proportional to allow the cell growth and moldability to ll the defective regions are some of the essential requirements for tissue engineering. 8 The hydrogels can be prepared from both natural and synthetic polymers by physical (polyelectrolyte complexation, hydrogen bonding and hydrophobic association) or chemical (free radical polymerization, irradiation crosslinking) methods.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, collagen injections were administered at 1-week-old rat infarcts and it was observed that infarct thickness, stroke volume and ejection fraction have increased compared to the control (saline injection) [6]. Suuronen E.J.…”
Section: Collagenmentioning
confidence: 99%
“…Molecules (with repair and/or regeneration capacities of the damaged tissue) are encapsulated in the hydrogel and released locally over time (the hydrazone bond is then broken and occurs the molecules release from nanoparticles). In several studies it was reported that polymer matrices can be used to sustain the release of encapsulated molecules for up to 100 days and the release profi le initially showed a quick release followed by a slower release rate [6][7][8][9][10]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, injectable hydrogels also preserve cardiac function when administrated without cells, demonstrating that the cells may not be responsible [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. For instance, promising preliminary results obtained in rodents and pigs using alginate [45,46] led to the first clinical trials in MI patients (NCT00557531 and NCT01226563) [55].…”
Section: Injectable Nanomaterialsmentioning
confidence: 99%